Bhima slays Dushasana - Mahabharata_57 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in Event depicted from Mahabharata: Bhima slays Duhshasana. Draupadi stands by and ties her hair after her vow is fulfilled of washing it with Duhshasana’s blood, which she had taken when he has tried to disrobe her in public in court.